The importance of re-reading. The interview with Louis H. Falik ten years after - Cristina Richieri (Formazione & Insegnamento, 2019)
This interview was given by Louis H. Falik, a scholar deeply involved in Feuerstein’s work, during a workshop which took place at Centro Feurstein c/o Centro Interateneo per la Ricerca Didattica e la Formazione Avanzata at Ca ‘ Foscari University in 2007. The event was both a workshop on LPAD (Learning Propensity Assessment Device) Standard 1, and a session for the certification of trainers in the Feuerstein Instrumental Enrichment Programme. At the time, it was decided to publish the Italian version of the interview in order to contribute to the circulation of Feuerstein’s learning theories in Italy. After over ten years, the interview is still thought-provoking given the diffusion and generativity of Feuerstein’s work in Italy − as some very recent publications testify – and in the light of Falik’s very personal project on the possible adaptation of Feuerstein’s learning theories for use with the elderly. These are the reasons for presenting the English version of that interview here below.